ITR e IPTU : o contraste entre as finalidades sociais e a gestão praticada - Leão, Celina Gontijo (2015)
The taxation is a crucial public policy to the performance of the State, because all other public policies depend on the revenues resulting from it. But taxation is not only the source of funding for the state; how taxation management performed brings several consequences for society, the function called extrafiscal tribute. In both features, fiscal and extrafiscal, taxation policy is subject to the constitutional principles, among which stand out the social function of property and the contribution as of the contributive ability which are intended to reach the state goal of building a society more justice and solidarity. The objective of this study is to analyze the quality of Brazilian taxation from the perspective of ITR (rural property tax) and IPTU (building and urban land ownership tax), from legislative management until the supervision and collection management, to ensure if they are respecting the principles mentioned. The hypothesis is that Brazilian tax is a regressive system, a system in which a citizen who has less financial capacity is tax more painfully than that accumulates assets, especially real estate heritage, because charges proportionately more taxes on consumption than on the property. This feature would be causing extrafiscal consequences of concentration of heritage and income and an unproductive use of land, consequences contrary to the constitutional goal of solidarity and the social function property. To do this analysis, through literature review, the second chapter will be discussed the issue backdrop for the purpose of work is to know what is the relationship between state and private ownership that justifies taxation and if this can lead to fiscal solidarity. Depending on the answer to that question, it can deploy a taxation aiming only raise, regardless of who pays, or taxation that considers all the social implications of tax collections. In the third chapter will be carried out the study of the principles of the social function of property and fiscal capacity, the changes their meanings throughout history, their predictions in others countries, to get the interpretation of these principles that better fulfills the constitutional state goals. Finally, in the fourth and fifth chapters will be reviewed taxes on real estate assets, ITR and IPTU, to check if its impact, in practice, respect the constitutional principles. From all the above, it is conclude that taxation management in Brazil is inefficient, contrary to the principles those should be obedience, because the taxation of real estate heritage does not reach the people who really have ability to pay, in addition to allowing the speculative use of urban and rural land, leaving the purposes of housing, feeding and equity in the background. The current taxation policy, highly regressive, contributes to increasing social inequality in the country and the absence of tax citizenship of the Brazilian population.